Сільськогосподарська дослідна справа у творчій спадщині академіка АН УРСР А.М. Гродзинського - Vergunov, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The contribution of academician of the Academy of Sciences of USSR A.M. Grodzinskiy (1926–1988) to the development of theory and practice of plantgrower and soil science is exposed by the method of historical and scientific analysis.